2018
DOI: 10.1016/j.micinf.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3 opsonization of Chlamydia trachomatis facilitates uptake in human monocytes

Abstract: Chlamydia trachomatis is an obligate intracellular bacterium that causes severe infections, which can lead to infertility and ectopic pregnancy. Although both innate and adaptive immune responses are elicited during chlamydial infection the bacterium succeeds to evade host defense mechanisms establishing chronic infections. Thus, studying the host-pathogen interaction during chlamydial infection is of importance to understand how C. trachomatis can cause chronic infections. Both the complement system and monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…trachomatis is opsonized by the complement C3 fragment iC3b which is recognized by CR3 expressed on monocytes and macrophages [58,59]. We recently demonstrated that complement C3 facilitates rapid uptake of C. trachomatis in human monocytes supporting the role for CR3 in chlamydial uptake, [59].…”
Section: Accepted Manuscriptmentioning
confidence: 80%
See 2 more Smart Citations
“…trachomatis is opsonized by the complement C3 fragment iC3b which is recognized by CR3 expressed on monocytes and macrophages [58,59]. We recently demonstrated that complement C3 facilitates rapid uptake of C. trachomatis in human monocytes supporting the role for CR3 in chlamydial uptake, [59].…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…trachomatis is opsonized by the complement C3 fragment iC3b which is recognized by CR3 expressed on monocytes and macrophages [58,59]. We recently demonstrated that complement C3 facilitates rapid uptake of C. trachomatis in human monocytes supporting the role for CR3 in chlamydial uptake, [59]. After macrophage entry C. trachomatis can induce a state of persistency, where the bacterium is viable and metabolic active, but does not replicate [1,22,63].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…Grids were blotted dry on filter paper and investigated using a Jeol 1010 transmission electron microscope (Jeol, Tokyo, Japan). Gold deposition was quantified as previously described (47). Briefly, a minimum of seven random fields were imaged for each grid containing at least 12 chlamydial organisms in total.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting. SDS-PAGE and Western blotting were performed essentially according to Lausen et al (47). Briefly, purified C. pneumoniae EBs were incubated in 50% serum for 30 min at 37°C, and unbound complement was removed by washing three times in PBS, with centrifugation at 15,000 ϫ g for 15 min between each wash.…”
Section: Discussionmentioning
confidence: 99%